DOI: 10.33915/etd.5087
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Intelligent Transportation Systems on Parallel Hybrid Electric Heavy Duty Vehicles

Abstract: Impact of Intelligent Transportation Systems on Parallel Hybrid Electric Heavy Duty Vehicles Ahmed Al-Samari A hybrid electric vehicle uses multiple sources of energy that can be independently or all together used to propel the wheels. In the presented work, the vehicle propulsion controller (VPC) for a parallel heavy duty hybrid electric vehicle (HEV) model has been modified to manage the alternative power source in advance based on the forthcoming traffic information. The goal is to prepare the powertrain fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Additionally, environmental pollution associated with nonrenewable energy sources has contributed to the need for alternative energy sources. Consequently, researchers globally are actively seeking solutions to reduce our dependence on non-renewable fossil fuels and transition to sustainable energy alternatives [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, environmental pollution associated with nonrenewable energy sources has contributed to the need for alternative energy sources. Consequently, researchers globally are actively seeking solutions to reduce our dependence on non-renewable fossil fuels and transition to sustainable energy alternatives [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…The study concluded that future investigation would be required but found that a prediction window larger than 15s started to degrade performance. Research by Al-Samari [33] was applied to a parallel hybrid electric vehicle using a looking-ahead strategy. The author showed that look-ahead strategy can give a chance for reducing the hybridization equipment sizes with improved fuel economy in comparison to the original equipment sizes without a look-ahead strategy.…”
Section: Real-time Optimization Hybrid Algorithmsmentioning
confidence: 99%